Production of Analog Rice from Cassava, "Goroho" Banana and Sago - Mamuaja, Christine F.; Lamaega, Jolanda Ch. E. (Jurnal Ilmu dan Teknologi Pangan, 2015)
Various diversification of food has been done to substitute rice with other staple ingredients. One of them is subtitute rice with analog rice from flour material. Local food ingredients at North Sulawesi Province especially at North Minahasa Regency potentially for analog rice are cassava, "goroho" banana, and sago. In this research, analog rice is the combination of cassava, "goroho" banana, and sago. Aims of these research are to utilize many local food ingredients at North Sulawesi Province, to utilize local food ingredients to produce analog rice from cassava, "goroho" banana, and sago, and to introduce to the community of North Minahasa Regency about analog rice (cassava, "goroho" banana, and sago). In this research, organoleptic test was done for four kinds of formula of analog rice, then those formula analyse in laboratory and in action research to community in 3 stages. First stage was to create analog rice. Second stage was to analyse analog rice chemically and third stage was action research of analog rice production to community at Airmadidi Sub District and Kalawat Sub District, North Minahasa Regency, North Sulawesi Province. Keywords : food diversification, analog rice, local food ingredients